2007
DOI: 10.1021/es070792y
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Compounds in the Cape Fear Drainage Basin in North Carolina

Abstract: Concern over perfluorinated organic compounds (PFCs), e.g., perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), is due to a number of recent studies which show that the PFCs are persistent, bioaccumulative, and toxic in animals. Despite sustained interest in this topic, little information is available concerning the environmental distributions of the compounds. In this study, a new method was developed for the analysis of 10 target PFCs and its performance was examined in a systematic evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
78
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 20 publications
16
78
2
Order By: Relevance
“…This phenomenon has also been reported in studies in New York [19], Kentucky and Georgia [24], and also in Denmark [25]. Earlier studies in New York (NY), Cleveland (OH) and North Carolina have reported that the PFOA concentrations were about several hundreds of ng/L in the effluents in WWTPs [14,19,26,27]. In our study from the seven WWTPs, the PFOA concentrations were much higher in wastewaters from plants QH and JXQ than those from the other plants, while the lowest PFOA was found in plant FZ.…”
Section: Pfcs In Wastewaterssupporting
confidence: 69%
“…This phenomenon has also been reported in studies in New York [19], Kentucky and Georgia [24], and also in Denmark [25]. Earlier studies in New York (NY), Cleveland (OH) and North Carolina have reported that the PFOA concentrations were about several hundreds of ng/L in the effluents in WWTPs [14,19,26,27]. In our study from the seven WWTPs, the PFOA concentrations were much higher in wastewaters from plants QH and JXQ than those from the other plants, while the lowest PFOA was found in plant FZ.…”
Section: Pfcs In Wastewaterssupporting
confidence: 69%
“…A systematic investigation of the Kanzaki River system by our group revealed that there is a single source of PFOA within the Ai River [17], which was confirmed by Nguyen et al [21]. The concentrations of PFOA in other countries are also shown in Table 1 [24][25][26][27]. These values are relatively higher than the values in Japan, excluding the Kansai region.…”
Section: Distributions Of Pfoa and Pfos In The Water Environment In Jsupporting
confidence: 67%
“…The levels of PFOS and PFOA in the Yangtze and Pearl Rivers (So et al, 2007) were of the same order of magnitude with those measured in the Po River, Italy (2e12 ng/L and 2e237 ng/L) (Loos et al, 2008), the Ruhr River (5.0 and 48.0 ng/L) in Germany (Skutlarek et al, 2006) and the Cape Fear River basin (28.9 and 12.6 ng/L) in North Carolina, USA (Nakayama et al, 2007).…”
Section: Riverssupporting
confidence: 63%